2013
DOI: 10.1111/echo.12325
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Work in Patients with Stable Chronic Heart Failure: Factors Associated and Prognostic Role

Abstract: In CHF patients, LAKE is significantly higher than in healthy controls, the prevalence of abnormally high LAKE is near fivefold higher in the former than in the latter. LAKE depends on systolic LV and renal function and is a strong predictor of CV death and hospitalization for HF. LA work has an incremental prognostic value over LA size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…LAKE is five times higher in patients with chronic HF (CHF) than in healthy controls. It depends on LV performance and renal function, and it is a strong predictor of cardiovascular events and hospitalisation for HF . Independently of HF aetiology, diastolic dysfunction is the strongest stimulus to increase LA size and work.…”
Section: Integrated Imaging Evaluationmentioning
confidence: 99%
“…LAKE is five times higher in patients with chronic HF (CHF) than in healthy controls. It depends on LV performance and renal function, and it is a strong predictor of cardiovascular events and hospitalisation for HF . Independently of HF aetiology, diastolic dysfunction is the strongest stimulus to increase LA size and work.…”
Section: Integrated Imaging Evaluationmentioning
confidence: 99%
“…The sheer number of measures of LA function (.20) generates confusion and hinders comparability of published studies. The reproducibility of these measures may also be an issue that threatens the robustness of these B (Asymptomatic structural heart disease) † LA peak reservoir strain measured within 48 h of admission for acute myocardial infarction is associated with the composite outcome of death and HF 13 † LA function independently predicts HF hospitalization among patients with coronary artery disease and preserved LVEF 14 † LA pump function is the strongest predictor of major adverse cardiac events and all-cause mortality in patients with chronic hypertension 15 † LAEF is associated with risk of new-onset AF independent of clinical risk factors, LV systolic/diastolic function, and LA volume in elderly persons referred for echocardiography 16 † LA ejection force is associated with risk of cardiovascular events independent of age, risk factors, LV geometry, and LV diastolic function in a population with pre-clinical risk factors such as hypertension and diabetes 17 † LA strain occurs in hypertensive and diabetic patients even prior to development of overt LA dilatation 18 C (Symptomatic HF) HFpEF † LA kinetic energy predicts cardiovascular death and HF hospitalization in chronic HF regardless of EF, and has an incremental prognostic value over LA size 19 † Blunted increase in mitral annular A' velocity during exercise distinguishes HFpEF from asymptomatic hypertensive patients 20 † LAEF at rest and blunted LA systolic reserve with isometric handgrip distinguish HFpEF from asymptomatic hypertensive LV hypertrophy 21 † LA dysfunction relates to symptom onset in HFpEF 22 and occurs even in the absence of overt LA enlargement 23 † LA strain is independently associated with exercise capacity in HFpEF 24 † LA pump function is an independent correlate of HF symptoms in hypertrophic cardiomyopathy 5 …”
mentioning
confidence: 99%
“…Previous studies on patients with mild-to-moderate heart failure symptoms have shown that higher LA contractile or ejection force and greater kinetic energy may exist in these patients compared with healthy people ( 17 , 30 ), possibly as compensation for maintaining resting cardiac output ( 31 , 32 ). Our study showed that greater fat depots surrounding LA, especially interatrial fat, was accompanied by decreased reservoir function though augmented LA kinetic energy and ejection force.…”
Section: Discussionmentioning
confidence: 98%